The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3897/zookeys.954.52254
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies on the genus Ectatosticta (Araneae, Hypochilidae) from China, with descriptions of two new species

Abstract: Species of the spider family Hypochilidae Marx, 1888 from China are studied, including two known species and two new species of the genus Ectatosticta Simon, 1892. The new species are E. wukongsp. nov. (♂♀) from Sichuan and E. xuanzangsp. nov. (♀) from Tibet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Hypochilus spiders construct a mesh web resembling a lampshade attached to a rock overhang and the spider rests in the middle of the web (called “lampshade web”; Forster et al., 1987). Ectatosticta spiders construct sheet webs among rocks or tree trunks (Lin & Li, 2020). Marx (1888) who described the first hypochilid, Hypochilus thorelli Marx, 1888, remarked that this spider “is so anomalous that it appears like the representative of a prototype, in which characters were united in one individual which are now distributed into widely differing genera”.…”
Section: Resultsmentioning
confidence: 99%
“…Hypochilus spiders construct a mesh web resembling a lampshade attached to a rock overhang and the spider rests in the middle of the web (called “lampshade web”; Forster et al., 1987). Ectatosticta spiders construct sheet webs among rocks or tree trunks (Lin & Li, 2020). Marx (1888) who described the first hypochilid, Hypochilus thorelli Marx, 1888, remarked that this spider “is so anomalous that it appears like the representative of a prototype, in which characters were united in one individual which are now distributed into widely differing genera”.…”
Section: Resultsmentioning
confidence: 99%
“…Hypochilus spiders construct a mesh web resembling a lampshade attached to a rock overhang and the spider rests in the middle of the web (called "lampshade web"; . Ectatosticta spiders construct sheet webs among rocks or tree trunks (Lin & Li, 2020). Marx (1889) who described the first hypochilid-Hypochilus thorelli Marx, 1888, remarked that this spider "is so anomalous that it appears like the representative of a prototype, in which characters were united in one individual which are now distributed into widely differing genera".…”
Section: Hypochilidae and Filistatidaementioning
confidence: 99%
“…These two species are known from the northern Qinghai-Tibet Plateau. However, recent discoveries ( Lin & Li, 2020 , 2021 , Wang et al, 2021 ) have confirmed considerable Ectatosticta diversity in the southern Qinghai-Tibet Plateau, with higher species richness and wider distribution than that of Hypochilus in the USA. Thus, we conducted an in-depth study of Ectatosticta to challenge the Wallacean and Linnean shortfalls.…”
mentioning
confidence: 99%